1992
DOI: 10.1182/blood.v80.7.1838.1838
|View full text |Cite
|
Sign up to set email alerts
|

Acute graft-versus-host disease: analysis of risk factors after allogeneic marrow transplantation and prophylaxis with cyclosporine and methotrexate [see comments]

Abstract: Previous studies of risk factors for acute graft-versus-host disease (GVHD) involved patients receiving predominantly single-agent prophylaxis. Therefore, a retrospective analysis was performed on 446 patients, from a single institution, who received transplants of marrow from HLA-identical siblings and the combination of cyclosporine (CSP) and methotrexate (MTX) to determine risk factors for acute GVHD associated with this more effective form of GVHD prophylaxis. The incidences of Grades II-IV and Grades III-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(42 citation statements)
references
References 0 publications
4
36
1
Order By: Relevance
“…Previous investigators have reported high early mortality rates in patients transplanted for advanced-phase CML (Apperley et al, 1988;Goldman et al, 1986Goldman et al, , 1988Martin et al, 1988;Thomas et al, 1986) as well as relapsed or refractory acute leukaemia (Doney et al, 1981;Marmont et al, 1991). The association of advanced leukaemia and the occurrence of severe GVHD has also been reported by Nash et al (1992). Cumulative effects of prior chemotherapy and reduced tolerance of the intensive conditioning regimens used at BMT (Biggs et al, 1992;Bortin et al, 1981;Clift et al, 1987Clift et al, , 1990Clift et al, , 1991Deeg et al, 1991;Nash et al, 1992) may account in part for the severe GVHD seen in patients transplanted for advanced leukaemia.…”
Section: Discussionmentioning
confidence: 93%
“…Previous investigators have reported high early mortality rates in patients transplanted for advanced-phase CML (Apperley et al, 1988;Goldman et al, 1986Goldman et al, , 1988Martin et al, 1988;Thomas et al, 1986) as well as relapsed or refractory acute leukaemia (Doney et al, 1981;Marmont et al, 1991). The association of advanced leukaemia and the occurrence of severe GVHD has also been reported by Nash et al (1992). Cumulative effects of prior chemotherapy and reduced tolerance of the intensive conditioning regimens used at BMT (Biggs et al, 1992;Bortin et al, 1981;Clift et al, 1987Clift et al, , 1990Clift et al, , 1991Deeg et al, 1991;Nash et al, 1992) may account in part for the severe GVHD seen in patients transplanted for advanced leukaemia.…”
Section: Discussionmentioning
confidence: 93%
“…Graft-versus-host disease (GVHD) is the most common cause of non-relapse mortality post-haematopoietic progenitor cell transplant (HPCT) (Lee et al, 2003). Acute GVHD (aGVHD) develops in 80% of recipients of unrelated HPCT and 30% of recipients of matched sibling HPCT (Nash et al, 1992). On the other hand, chronic GVHD (cGVHD) affects 20-50% of paediatric recipients several months post-HPCT (Baird et al, 2010).…”
mentioning
confidence: 99%
“…In addition, elderly people are more frequently diagnosed with high-risk AML as defined by recurring karyotypic abnomalities, including monosomies and complex aberrations, rendering them at an increased risk of relapse and treatment failure. Standard intensity conditioning at this age often leads to excessive organ toxicity as well as a high incidence of graft-versus-host disease (GvHD) (Nash et al, 1992). On the other hand, reduced-intensity conditioning results in an increased incidence of relapse especially in patients with residual marrow blasts (Alyea et al, 2006).…”
mentioning
confidence: 99%